2021
DOI: 10.1038/s41419-021-03432-1
|View full text |Cite
|
Sign up to set email alerts
|

HNRNPD interacts with ZHX2 regulating the vasculogenic mimicry formation of glioma cells via linc00707/miR-651-3p/SP2 axis

Abstract: Studies have found that RNA-binding proteins (RBPs) are dysfunctional and play a significant regulatory role in the development of glioma. Based on The Cancer Genome Atlas database and the previous studies, we selected heterogeneous nuclear ribonucleoprotein (HNRNPD) as the research candidate and sought its downstream targeted genes. In the present study, HNRNPD, linc00707, and specific protein 2 (SP2) were highly expressed, while zinc fingers and homeboxes 2 (ZHX2) and miR-651-3p were remarkedly downregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 55 publications
(39 reference statements)
0
23
0
Order By: Relevance
“…This study proved that miR-651-3p downregulation was related to the resistance of HCC cells to CDDP. Decreased miR-651-3p has been found in gastric cancer, and the proliferation and migration of the tumor cells can be effectively inhibited when miR-651-3p is overexpressed [ 13 ]. Therefore, it was hypothesized in this study that miR-651-3p involved the progression of HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study proved that miR-651-3p downregulation was related to the resistance of HCC cells to CDDP. Decreased miR-651-3p has been found in gastric cancer, and the proliferation and migration of the tumor cells can be effectively inhibited when miR-651-3p is overexpressed [ 13 ]. Therefore, it was hypothesized in this study that miR-651-3p involved the progression of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-124 downregulation is related to the stem formation and sorafenib resistance of HCC cells [ 12 ]. A previous study has identified miR-651-3p as a tumor inhibitor that can effectively suppress the progression of glioma cancer [ 13 ]. However, the role of miR-651-3p in HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although gliomas are relatively rare, they are aggressive tumors with high morbidity and mortality rates ( Ostrom et al, 2014 ). LncRNAs are aberrantly expressed in glioma tissues and cell lines and are thought to affect the occurrence and development of the tumor ( Peng et al, 2018 ; Yu et al, 2021 ). Recent studies have shown that GACAT3 is overexpressed in glioma tissues and is incrementally elevated during disease progression.…”
Section: Expression Of Gacat3 In Cancermentioning
confidence: 99%
“…LINC00707 is upregulated in disease such as lung cancer (Ma et al, 2018;Zhang et al, 2019;Shao et al, 2021), pneumonia (Zou et al, 2021), melanoma (Yang et al, 2018), colorectal cancer (CRC) (Shao et al, 2019;Zhu H. et al, 2019;Wang et al, 2020), glioma (Liu and Hu, 2020;Yu et al, 2021), clear cell renal cell carcinoma (Pang et al, 2020), breast cancer (BC) (Jiang et al, 2020;Yuan et al, 2020), osteosarcoma (Zhang et al, 2021), cervical cancer (Guo et al, 2021), bladder cancer (Gao and Ji, 2021), ovarian cancer (Guo et al, 2021), gastric cancer (Xie et al, 2019), hepatocellular carcinoma (Tu et al, 2019;Wang et al, 2019), and SCI (Zhu S. et al, 2019). LINC00707 dysregulation contributes to the process of osteogenic differentiation (Jia et al, 2019;Cai et al, 2020;Liu J. et al, 2020) of HBMSCs.…”
Section: The Expression and Role Of Linc00707 In Diseasementioning
confidence: 99%
“…LINC00707 is overexpressed in glioma tissues (Liu and Hu, 2020;Yu et al, 2021) and cells. This high expression is associated with poor glioma clinicopathological parameters, including Karnofsky performance status score and WHO grade (Liu and Hu, 2020).…”
Section: Gliomamentioning
confidence: 99%